The answer would be -4
Hope this helps
Answer:
9
b³
Step-by-step explanation:
The 2 terms are like terms and can be combined, that is
b³ ( 1 + 8)
= 9
b³
The constants of a polynomial is the term that has no variable attached to it.
<h3>The constant term</h3>
To determine the constant, we simply multiply the constant term in each factor of the polynomial.
So, we have:
<h3 /><h3>Polynomial P(x) = (x-2)(x-4)(x-5)</h3>
![Constant = -2 \times -4 \times -5](https://tex.z-dn.net/?f=Constant%20%3D%20-2%20%5Ctimes%20-4%20%5Ctimes%20-5)
![Constant = -40](https://tex.z-dn.net/?f=Constant%20%3D%20-40)
Hence, the constant is -40
<h3>Polynomial P(x) = (x-2)(x-4)(x+5)</h3>
![Constant = -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = 40](https://tex.z-dn.net/?f=Constant%20%3D%2040)
Hence, the constant is 40
<h3>Polynomial P(x) =1/2(x-2)(x-4)(x+5)</h3>
![Constant = \frac 12 \times -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%20%5Cfrac%2012%20%5Ctimes%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = 20](https://tex.z-dn.net/?f=Constant%20%3D%2020)
Hence, the constant is 20
<h3>Polynomial P(x) = 5(x-2)(x-4)(x+5)</h3>
![Constant = 5 \times -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%205%20%5Ctimes%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = 200](https://tex.z-dn.net/?f=Constant%20%3D%20200)
Hence, the constant is 200
<u>P(x) =-5(x-2)(x-4)(x+5)</u>
![Constant = -5 \times -2 \times -4 \times 5](https://tex.z-dn.net/?f=Constant%20%3D%20-5%20%5Ctimes%20-2%20%5Ctimes%20-4%20%5Ctimes%205)
![Constant = -200](https://tex.z-dn.net/?f=Constant%20%3D%20-200)
Hence, the constant is -200
Read more about polynomials at:
brainly.com/question/2833285
Point Form: (1,-5)
Equation Form: x-1,y=-5
Answer:
D) -122
Step-by-step explanation:
Given:
![f(x) = 2x^3-\frac{3}2x](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%5E3-%5Cfrac%7B3%7D2x)
We need to find f(-4).
Now by substituting the value of x =-4 in above equation we get;
![f(-4)= 2\times(-4)^3-\frac{3}{2}\times(-4)\\](https://tex.z-dn.net/?f=f%28-4%29%3D%202%5Ctimes%28-4%29%5E3-%5Cfrac%7B3%7D%7B2%7D%5Ctimes%28-4%29%5C%5C)
By using PEDMAS we will solve for exponential function first we get;
Now we know that ![(-4)^3=-64](https://tex.z-dn.net/?f=%28-4%29%5E3%3D-64)
So we get;
![f(-4)= 2\times(-64)-\frac{3}{2}\times(-4)\\](https://tex.z-dn.net/?f=f%28-4%29%3D%202%5Ctimes%28-64%29-%5Cfrac%7B3%7D%7B2%7D%5Ctimes%28-4%29%5C%5C)
Now using PEDMAS we will solve division.
![f(-4)= 2\times(-64)-1.5\times(-4)](https://tex.z-dn.net/?f=f%28-4%29%3D%202%5Ctimes%28-64%29-1.5%5Ctimes%28-4%29)
Now using PEDMAS we solve multiplication.
![f(-4)= -128+6](https://tex.z-dn.net/?f=f%28-4%29%3D%20-128%2B6)
Finally by subtraction we get;
![f(-4)= -122](https://tex.z-dn.net/?f=f%28-4%29%3D%20-122)